Navigating Bilingualism: Language, power, and the social identity construction of the first Saudi elementary students to receive English language instruction - Ghanem Alghuwainem (Ampersand)
This study examines the influence of the expanded English language curriculum on social identity construction among elementary students in Saudi Arabia. Interviews were conducted with five elementary school teachers in Al-Hassa governorate and analyzed through thematic coding. From this, three main themes emerged: teachers' perceptions of English learning's significance, factors influencing language resistance, and the impact on students' identity. Results indicate that English is perceived not only as crucial for academic and professional success but also as integral to Saudi Arabia's Vision 2030 for modernization and globalization. However, resistance to English due to cultural and socioeconomic factors suggests a disparity between national ambitions and student perceptions, highlighting the challenge in Saudi Arabia of aligning educational strategies with the broader goals of societal development and integration into the global community.